Haploinsufficiency of progranulin causes mitochondrial dysfunction - Bautista, Javier S.; Falabella, Micol; Lu, Shanti; Rohrer, Jonathan D.; Plun‐Favreau, Helene; Wray, Selina; Taanman, Jan‐Willam; Pitceathly, Robert D. S.; Pitceathly, Robert D.S. (Alzheimer's & dementia, 2023)
Background Frontotemporal dementia (FTD) is the second most common cause of young‐onset dementia, caused by nerve loss in the frontal and temporal lobes. Mutations in the progranulin (GRN) gene are one of the leading causes of FTD, resulting in a happloinsufficiency of the soluble protein progranulin (PGRN). However, the effect of PGRN happloinsufficiency on mitochondrial activity has not been explored in FTD. Method A stable GRN knockdown was generated in H4 neuroglioma cells using a lentiviral shRNA vector. Mitochondrial DNA and RNA transcripts were measured by quantitative polymerase chain reaction (qPCR), protein expression by Western Blot analysis, and bioenergetics profile by Seahorse analysis and Native PAGE. Result In the H4 model, PGRN deficiency induced a bioenergetic impairment, indicating a mitochondrial defect. The activity of the complexes of the electron transport chain was decreased. In addition, we observed impaired mitochondrial genomics. Conclusion These results suggest that PGRN happloinsufficiency may play a role in mitochondrial homeostasis, which may be contributing to the development of FTD. Future work will involve characterising the mitochondrial mechanism, and further validating these findings in FTD patient samples.